2020
DOI: 10.1158/1055-9965.epi-20-0300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metabolic Syndrome on Risk of Breast Cancer: A Study Analyzing Nationwide Data from Korean National Health Insurance Service

Abstract: Background: To investigate the influence of metabolic syndrome and its components on the risk of breast cancer.Methods: Retrospective nationwide cohort study analyzing data of 13,377,349 women older than 19 years from Korean National Health Insurance Service was performed. Cox proportional hazards model was used to calculate HR and 95% confidence interval (CI) of breast cancer risk.Results: The presence of metabolic syndrome decreased the risk of all breast cancer types in all subjects (HR, 0.954; 95% CI, 0.93… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
4
6
0
2
Order By: Relevance
“…An increasing number of MS components positively correlated with a significant increase in cancer risk in adjusted models, except for non-Hodgkin lymphoma and prostate, lung and pre-menopausal breast cancer. The observed effect sizes for the cancers associated with MS in our data were broadly consistent with previous studies [7,9,[13][14][15][28][29][30][31][32][33][34]. Contrary to our study, Park et al reported a weaker association between MS and thyroid cancer [14], while Almquist and colleagues failed to report any association [35] using a z-score (standard score) calculation that included all 5 components of MS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…An increasing number of MS components positively correlated with a significant increase in cancer risk in adjusted models, except for non-Hodgkin lymphoma and prostate, lung and pre-menopausal breast cancer. The observed effect sizes for the cancers associated with MS in our data were broadly consistent with previous studies [7,9,[13][14][15][28][29][30][31][32][33][34]. Contrary to our study, Park et al reported a weaker association between MS and thyroid cancer [14], while Almquist and colleagues failed to report any association [35] using a z-score (standard score) calculation that included all 5 components of MS.…”
Section: Discussionsupporting
confidence: 91%
“…In the case of gynaecological cancers, menopausal status was a determinant factor, especially in breast cancer. In agreement with previous studies, we observed that MS increased breast cancer risk in post-menopausal women, and decreased it in pre-menopausal women [7,29]. Previous investigations proposed that each component of the metabolic syndrome is connected with systemic alterations.…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…Guo’s meta-analysis of 17 follow-up studies with 602,195 women concluded that postmenopausal women with MetS were associated with a significantly increased risk of BC incidence (adjusted risk ratio = 1.25, 95% CI 1.12–1.39) [ 14 ]. According to a recent Korean cohort study of 13,377,349 women using NHIS, MetS increased the risk of all BC types (HR 1.15, 95% CI 1.12–1.17) in women aged >50 years [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freshmen will have many negative psychological emotions, such as depression, anxiety, loneliness, etc., resulting in no interest in learning, unwillingness to communicate with others, etc. [5]. At present, universities have to conduct psychological investigation on students when freshmen enter the university, which has also accumulated a large amount of psychological data.…”
Section: Introductionmentioning
confidence: 99%